Seroprevalence of Hepatitis B Virus Infection and Associated Factors among Cancer Patients at Hawassa University Comprehensive Specialized Hospital, Ethiopia - Nadew, Surafel; Seyoum Wendimagegn, Zeru; Bizuneh, Tinsae; Bogale, Netsanet; Fenta Feleke, Sefineh; Mulu Yayeh, Berihun; Birhanu Worku, Atsede; Mulugeta Kassaw, Genanew; Awoke, Mulat; Nigatu, Amare; Tesfa, Natnael Amare (The Journal of Infection in Developing Countries, 2024)
Introduction: Hepatitis B virus infection is a global public health concern and has a high degree of associated morbidity and mortality. In Ethiopia, Hepatitis B virus infection has a variable seroprevalence among different regions with an estimated overall prevalence of around 6%. However, there is a scarcity of data specific to cancer patients. Methodology: A hospital-based cross-sectional study was conducted among 384 cancer patients who came for follow-up at the oncology unit of Hawassa University Comprehensive Specialized Hospital from January 1/2020 to October 11/2021. A systematic sampling technique was employed to select the participants. Data was collected using structured and interviewer-administered questionnaires and blood samples were drawn from the patients to test hepatitis B virus sero-status. Data was entered to Epi- Data version 4.6 then exported and analysis was done using SPSS version 25. Descriptive statistics were used to describe the study participants. Finally, bivariable and multivariable binary logistic regression was used to identify significantly associated factors. Results: The seroprevalence of hepatitis B virus infection among cancer patients was 7.6% [95% CI: (4.54 - 9.79)]. Having multiple sexual partners (AOR = 6.24, 95% CI (3.35-16.80)), a history of dental procedures (AOR = 3.34; 95% CI (1.007‑7.66)), and being a hepatocellular carcinoma patient (AOR = 6.13; 95% CI (3.66-18.77)) were factors associated with seropositive status for Hepatitis B virus. Conclusions: The seroprevalence of Hepatitis B virus infection among cancer patients was high. It is better to consider HBV screening in cancer patients and doing cancer surveillance in HBV-infected patients.